Instructional Media Development “Dakon” to Improve Speaking Skill OF SMA Negeri 5's 10th Grade Students - Bagas Ilham Ardiansyah; Deddy Kurniawan (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2019)
This research and development aims to develop an Android-based learning media “DaKon” to train the speaking skill of tenth grade students in SMAN 5 Malang. The development model used in this research is a Production of Multimedia Packages from Ghislandi. The procedure as mentioned above includes (1) define the user needs, (2) design product, (3) data preparation, (4) arrange product, (5) system alignment and evaluation, (6) produce product. Based on the results of the questionnaire and the observation with qualitative method, the Android application “DaKon” can be used as a learning media to practice speaking skill of the tenth grade students in senior or vocational high school.